RESPONSIVITAS PROGRAM JAMINAN KESEHATAN SOSIAL (JAMKESOS) (STUDI KASUS DI DUSUN BLALI, KABUPATEN BANTUL) - Evi Zubaidah (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
Social health insurance (Jamkesos) is organizing the Yogyakarta Provincial health care insurance that provides health insurance and are able to meet basic health needs for the population in the province in a sustainable manner so manifest optimal health degree equitably. As an institution that aims to provide maximal service to the community, the quality of service can be one of the responsiveness of the institution, so Bapel Jamkesos as a service provider, provides responsiveness to the expectations, desires, aspirations and demands of service users or the public, Accordingly, this study aimed to determine the responsiveness of Jamkesos Program to the community with a case study in the hamlet Blali, Bantul. The results of this study indicate that Jamkesos in the implementation of the program has a pretty good responsiveness, as Jamkesos can provide services according to the needs and aspirations of the community, although there are still many shortcomings in implementation. To measure indicators of the responsiveness of the program Jamkesos obtained from the writing and analysis of several indicators, namely (1) Procedure Guarantee and claims, (2) Procedures Socialization Program Jamkesos DIY, (3) Quality of the Program jamkesos DIY, (4) Community (as the Target Group ) of the four indicators of responsiveness, no visible positive impact on the number of Jamkesos utilization, and the negative impact of the lack of information received by the community of participants Jamkesos.